Manajemen Internalisasi Nilai Pendidikan Agama Islam di Sekolah Dasar: Strategi Sekolah Melalui Program 5S - Ashoumi, Hilyah; Syarifah, Putri (Universitas Pesantren Tinggi Darul 'Ulum, 2018)
This article aims to describe and explore the internalization of the value of PAI in SD Plus Rahmat Kediri through school strategies and programs as well as supporting and inhibiting factors in realizing religious culture through exemplary and habituation. The approach taken is a qualitative approach through a case study design so that the data is analyzed through data collection, data reduction, data presentation, and conclusion/data verification. School strategies and programs as an effort to internalize the value of PAI are carried out in the presence of several programs: 5S; prayer in congregation; memorize short letters and recite the al-Qurâ€™Än using the ummÄ« method; pray when going to start activities and end activities; and exemplary and habitual morality. The role of school people and parents becomes meaningful support for the implementation of this program, obstacles appear in some parents who have different vision and mission of education with the school, teacher assistance that is not optimal in every religious activity and school facilities does not support the development of religious culture efforts are made to make improvements including musala. Therefore, good relations and cooperation between all parties are needed to create an institution that internalizes the values of Islamic religious education.